Frame Retransmissions Considered Harmful: Improving Spectrum Efficiency Using Micro-ACKS - Zhang, Jiansong; Shen, Haichen; Tan, Kun; Chandra, Ranveer; Zhang, Yongguang; Zhang, Qian (ACM MobiCom, 2012)
Retransmissions reduce the efficiency of data communication in wireless networks because of: (i) per-retransmission packet headers, (ii) contention overhead on every retransmission, and (iii) redundant bits in every retransmission. In fact, every retransmission nearly doubles the time to successfully deliver the packet. To improve spectrum efficiency in a lossy environment, we propose a new in-frame retransmission scheme using ACKs. Instead of waiting for the entire transmission to end before sending the ACK, the receiver sends smaller ACKs for every few symbols, on a separate narrow feedback channel. Based on these ACKs, the sender only retransmits the lost symbols after the last data symbol in the frame, thereby adaptively changing the frame size to ensure it is successfully delivered. We have implemented ACK on the Sora platform. Experiments with our prototype validate the feasibility of symbol-level ACK. By significantly reducing the retransmistion overhead, the sender is able to aggressively use higher data rate for a lossy link. Both improve the overall network efficiency. Our experimental results from a controlled environment and an 9-node software radio testbed show that ACK can have up to 140% throughput gain over 802.11g and up to 60% gain over the best known retransmission scheme.